Aktivisme Kelas Menengah Berbasis Media Sosial: Munculnya Relawan dalam Pemilu 2014 - Wasisto Raharjo Jati (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2016)
Emergence of voluntarism power that occured in 2014 election have indicated new form of middle class in Indonesia. Analyse on middle class always posited as either